2017
DOI: 10.1016/j.midw.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Midwives perceptions of partner presence in childbirth pain alleviation in Nigeria hospitals

Abstract: information from this study can improve midwifery practice and aid further research regarding midwives' attitudes, knowledge and usage of partner presence in pain management during childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Nighty-eight percent of providers believed that it was appropriate and important for a man to participate in RMNCAH services and support his female partner. This is consistent with previous ndings from hospitals in Nigeria where midwives acknowledged the bene ts of having a partner present, for example, contributing to pain relief during childbirth [49]. Previous studies have found that engaging men in reproductive, maternal, and newborn health can increase care seeking, improve home care practices, and support more equitable communication and decision-making among couples related to maternal and newborn health [1,27].…”
Section: Beliefs and Perceptionssupporting
confidence: 89%
“…Nighty-eight percent of providers believed that it was appropriate and important for a man to participate in RMNCAH services and support his female partner. This is consistent with previous ndings from hospitals in Nigeria where midwives acknowledged the bene ts of having a partner present, for example, contributing to pain relief during childbirth [49]. Previous studies have found that engaging men in reproductive, maternal, and newborn health can increase care seeking, improve home care practices, and support more equitable communication and decision-making among couples related to maternal and newborn health [1,27].…”
Section: Beliefs and Perceptionssupporting
confidence: 89%
“…A stable marital relationship, which was characterized as living with one's partner, was an independent factor connected with a higher score on the MCSRS. Furthermore, the partner's presence during childbirth may be a factor in pain relief, favoring labor progression and childbirth 23 …”
Section: Discussionmentioning
confidence: 99%
“…11 A 2019 Cochrane qualitative evidence synthesis reported that labour companions support women by acting as advocates, bridging communication gaps between health workers and women, and providing practical and emotional support (such as massages, encouraging mobility, praise and reassurance). 12 In the past decade, quantitative studies [13][14][15][16][17][18][19][20][21] have explored general perceptions and factors associated with labour companionship in maternity care (antenatal care, labour and childbirth and/or postnatal care), but to date have not explored the relationship between labour companionship and mistreatment. Furthermore, despite not always being integrated within studies that assess experience of care, 13 16 17 20 the perspective of the woman is imperative to design maternity care that responds to women's needs.…”
Section: Introductionmentioning
confidence: 99%